General decision making styles of military personnel (adaptation of the questionnaire) - Marozau, Alexander A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents a study of the decision-making styles of military personnel during adaptation of the English-speaking questionnaire «General decision making style» by S. J. Scott and R. A. Bruce. The problematic issues, which are characteristic of the research subject area in the decision-making styles, were noted. The theoretical foundations of the styles included in the questionnaire, under which the authors understand individual cognitive styles and show the relative simplicity of such an understanding, are disclosed. The questionnaire was translated into Russian, its content validity was evaluated with theparticipation of several experts, the analysis of the items, the evaluation of reliability by internal consistency (α-Cronbach) and the test-retest method was carried out, and various types of constructive validity (factor, convergent and discriminant) were tested. The obtained results are correlated with both foreign (regarding checking the questionnaire`s psychometric properties) and native (verification of the hypothesis of T. V. Kornilova on a single latent variable «Acceptance of uncertainty and risk» regarding the inclusion of intuitive abilities in it) scientists` studies. Relationships between the decision-making styles and intellectual and personal potential of servicemen, which is represented in our study by scales of the questionnaires«Tolerance for uncertainty», «Personal Factors of Decisions» T. V. Kornilova and «Reflectivity» A. V. Karpov, are demonstrated. The dominant decision-making styles of the mixed sample of servicemen was determined: rational and intuitive. The presented article allows to expand research tools of Belarusian and Russian psychology in the field of decision-making styles study. Study of the decision-making styles of different professional groups and its standardization, and with respect to the military – building a structural decision-making model for their various categories (cadets, sergeants, officers) is promising area for working with the questionnaire.
Keywords: decision-making style; questionnaire; adaptation; reliability; validity; military personnel